IMPLIKASI TEORI BIAYA PRODUKSI TERHADAP EFISIENSI USAHA MIKRO DI SEKTOR PERTANIAN - Andini, Pebri; Maisuuna Rahman, Khaalisah; Khairina Daulay, Tata; Syuriani Harahap , Evi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The agricultural sector plays an important role in supporting the national economy and serves as a primary source of livelihood for most Indonesian communities, particularly micro-scale entrepreneurs. However, micro enterprises in the agricultural sector still face various challenges in managing production activities, especially in controlling production costs which significantly affect business efficiency. This study aims to analyze the implications of production cost theory on the efficiency of micro enterprises in the agricultural sector. The research employs a descriptive qualitative approach using a literature study method by utilizing secondary data sources from national scientific journals, economics textbooks, and relevant research findings. The results indicate that production costs in agricultural micro enterprises are dominated by variable costs such as seeds, fertilizers, pesticides, and labor. Inefficient management of production factors can lead to cost inefficiencies that ultimately reduce business efficiency. The application of production cost theory can help entrepreneurs identify cost structures, determine the most efficient combination of production inputs, and improve business productivity. Therefore, a proper understanding of production cost theory can serve as an essential basis for improving the efficiency of micro enterprises in the agricultural sector, thereby increasing entrepreneurs' income and supporting the sustainability of agricultural business activities.